PENGEMBANGAN MODEL BUKU AJAR SEJARAH SASTRA INDONESIA MODERN BERPERSPEKTIF GENDER - Maman Suryaman (LITERA, 2013)
This study aims to describe lecturers’ and students’ perceptions of learning materials of the history of modern Indonesian literature with a gender perspective. Based on the perceptions, a conceptual model of a course book on the history of modern Indonesian literature with a gender perspective is designed. This study employed a development research design. The data were collected through interviews and a document study on information about characteristics of a course book on literature history with a gender perspective. The findings show that the lecturers’ and students’ perceptions of gender have not become a strong perspective in literature history learning. The books on literature history as learning references have not accommodated gender perspective issues. There is an opinion that female writers’ works do not belong to main works in the history of Indonesian literature.